2019
DOI: 10.1002/ecs2.2555
|View full text |Cite
|
Sign up to set email alerts
|

Marsh bird occupancy along the shoreline‐to‐forest gradient as marshes migrate from rising sea level

Abstract: One mechanism by which coastal marshes may persist as sea-level rises is to expand landward into existing forest, a process known as marsh migration. Though recent studies highlight the importance of marsh migration to the conservation of birds associated with coastal marshes, marsh bird responses to this transition from forest to marsh are poorly understood. To address this need, we conducted surveys of five focal marsh bird taxa at 92 points distributed across the gradient from the shoreline to the marsh-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…Recent research has investigated the ecological dynamics of upland to marsh transition and come up with broad descriptions of the mechanisms and trajectory of change in plant communities (Fagherazzi et al 2019, Kirwan and Gedan 2019, Taillie and Moorman 2019, Tully et al 2019). Within these frameworks, the ecotone or “transition zone” is an ephemeral state.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has investigated the ecological dynamics of upland to marsh transition and come up with broad descriptions of the mechanisms and trajectory of change in plant communities (Fagherazzi et al 2019, Kirwan and Gedan 2019, Taillie and Moorman 2019, Tully et al 2019). Within these frameworks, the ecotone or “transition zone” is an ephemeral state.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should also compare the occupancy and functional use of ghost forest and high marsh by additional taxonomic groups and consider additional functional and behavioral characteristics to determine the overall equivalency of ghost forest and high marsh. Although both saltmarsh species observed here used ghost forest habitat in approximately the same way as high marsh, specialist saltmarsh species may be incapable of migrating into new habitat or unable to use ghost forest habitat as effectively as existing marsh (Taillie & Moorman, 2019). More comprehensive knowledge of the response of critical marsh faunal groups to marsh migration is necessary for accurate evaluation of marsh extent.…”
Section: Discussionmentioning
confidence: 98%
“…This may include several bird species whose high marsh habitat is expected to decline with sea-level rise (e.g., rails and marsh sparrows; Hunter et al, 2015), most notably the saltmarsh sparrow, which has been predicted to go extinct by 2060 in the absence of effective marsh migration (Field et al, 2017). Certain saltmarsh bird species, however, are known to use newly migrated marsh less than existing high marsh (Taillie & Moorman, 2019). Because this study demonstrates the presence of saltmarsh arthropod prey in the ghost forest, previously observed differences in bird occupancy may be driven by differences in habitat structure between zones (Benoit & Askins, 1999), rather than arthropod prey availability.…”
Section: Discussionmentioning
confidence: 99%
“…Sawgrass flowered in the second year following the fire (Davison and Bratton, 1988). Tallie and Moorman (2019) found that a prescribed burn in a sawgrass marsh in North Carolina improved the quality and quantity of habitat for coastal marsh birds. Venne and Frederick (2013) found that great egrets (Ardea alba) and white ibises (Eudocimus alba) selected burned sites and deep sloughs in a sawgrass marsh and avoided dense, unburned sites.…”
Section: Firementioning
confidence: 99%